Socialization as Integrated Marketing Communication Strategy in Increasing Brand Awareness (Case study "Solo Destination" Application of Solo City Government) - Wijaya, Lina Sinatra; Vanel, Zon; Huwae, George Nicholas; Kristanto, Budhi (Petra International Journal of Business Studies, 2020)
The rapid development of technology makes a city government communicate with the community while building or improving its image. This condition provides its advantages for cities that have a good image, such as increasing the investors, revenue in the tourism sector and cities, and also the development of the cities. The purpose of this study is to socialize the Solo Destination Application to increase brand awareness of the society toward this application. This is descriptive qualitative research and the sample of the population is represented by 131 students from one junior high school, one senior high school and also 100 PKK (Family Welfare Organization) members in two sub-districts in Solo city. The result shows that to increase the awareness of the society in using the application, socialization should be done by the Solo city government to disseminate evenly to strategic targets such as to most of the junior/senior high schools, all the sub-districts citizens and also to other government offices in Solo as a whole. Besides, the use of word of mouth campaigns to ensure that the marketing strategy through social media such as Facebook and Instagram should also be put to the highest and best use.